A Remedial Action Scheme to Prevent Mid/Long-Term Voltage Instabilities - Khoshkhoo H.; Yari S.; Pouryekta A.; Ramachandaramurthy V.K.; Guerrero J.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Software testing; System stability; Electrical distance; Generation rescheduling; Long-term voltage instability; Normal operations; Remedial action scheme; Special protection system; Stability of power system; Voltage instability; Electric load shedding